PENINGKATAN KEMAMPUAN MOTORIK KASAR PADA ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL DANDA PADA KELOMPOK B DI TK AL-MUBARAK KECAMATAN TANETE RIATTANG BARAT KABUPATEN BONE - Ainun Mutmainnah; Bonita Mahmud; A. Sri Mardiyanti Syam (EDUCHILD (Journal of Early Childhood Education), 2025)
This thesis discusses the improvement of gross motor skills in early childhood through the traditional game of "danda" among Group B students at Al-Mubarak Kindergarten, Tanete Riattang Barat Subdistrict, Bone Regency. The purpose of this study is to determine the gross motor skills of early childhood children through danda play activities at Al-Mubarak Kindergarten in the Tanete Riattang Barat Subdistrict. This research is a quantitative study using a True Experimental Design with the one group pretest-posttest model, conducted at Al-Mubarak Kindergarten with a sample of 23 children. The study adopts a pedagogical approach. Data collection techniques involved observation and testing. The data obtained during the research were analyzed using SPSS for Windows version 22 to calculate descriptive statistics of the pretest and posttest, as well as the paired sample t-test. The results show that playing danda significantly improves the gross motor skills of early childhood children in Group B in the Tanete Riattang Barat Subdistrict. This is evidenced by the t-test results between the pretest and posttest scores, where the significance value obtained was 0.001 < 0.05. Therefore, it can be concluded that danda play activities effectively enhance the gross motor skills of early childhood children in Group B at Al-Mubarak Kindergarten, Tanete Riattang Barat Subdistrict.